The Effect of compound exercises using the (RANDOM SHOT) device and the electronc goal ln developing the speed of the motor response and the rapid ability of the two goal keepers youth football halls - Diana Haider; Dr. Widad Kadhum (الرياضة المعاصرة, 2021)
The research problem shaped through the entry of complex exercises with the introduction of scientific devices as a Random Shot, and the electronic goal when applying goalkeepers exercises for the national football team for halls. Through the experience of the researchers in the field and academic field, and on students, researchers and personal interviews with football coaches, as well as their follow up on the training course. The two researches noticed that there was a variation in the movement response and ability of the goalkeepers' feet. This may be attributed to the lack of interest of trainers in training these two abilities. As well as, the lack of equipment and tools that accompany exercises which allow for diversity and change to occur, it is regarded as one of the important rules in training.